2008
DOI: 10.1136/gut.2008.162404
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride (Resolor) in the treatment of severe chronic constipation in patients dissatisfied with laxatives

Abstract: Prucalopride significantly and consistently improved bowel function, associated symptoms and satisfaction in chronically constipated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
321
5
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(371 citation statements)
references
References 46 publications
31
321
5
14
Order By: Relevance
“…This analysis used integrated data from six phase 3 and 4, multicentre, double‐blind, randomised, placebo‐controlled, parallel‐group trials of the efficacy and safety of prucalopride in patients with chronic constipation, performed across three continents (Table 1; ClinicalTrials.gov identifiers: SPD555‐302 [NCT01147926], SPD555‐401 [NCT01424228], PRU‐CRC‐3001 [NCT01116206], PRU‐USA‐13 [NCT00485940], PRU‐USA‐11 [NCT00483886] and PRU‐INT‐6 [NCT00488137]) 11, 23, 24, 25, 26, 27. The designs of these trials were similar and have been described in detail previously 11, 23, 24, 25, 26, 27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis used integrated data from six phase 3 and 4, multicentre, double‐blind, randomised, placebo‐controlled, parallel‐group trials of the efficacy and safety of prucalopride in patients with chronic constipation, performed across three continents (Table 1; ClinicalTrials.gov identifiers: SPD555‐302 [NCT01147926], SPD555‐401 [NCT01424228], PRU‐CRC‐3001 [NCT01116206], PRU‐USA‐13 [NCT00485940], PRU‐USA‐11 [NCT00483886] and PRU‐INT‐6 [NCT00488137]) 11, 23, 24, 25, 26, 27. The designs of these trials were similar and have been described in detail previously 11, 23, 24, 25, 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…The designs of these trials were similar and have been described in detail previously 11, 23, 24, 25, 26, 27…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the correlation between aggregate measures of published studies addressing bowel patterns and pain correspond with results of a pilot study, which demonstrated a significant relationship between changes in bowel frequency and pain ratings for individual patients receiving linaclotide for constipation. 62 The described correlation between improved pain ratings were not only reported in studies of the newly introduced agents for IBS-C, [63][64][65][66][67] but were also observed in many other trials, which did not meet inclusion criteria for this analysis and examined the effects of interventions ranging from fiber supplements, 68,69 to herbal preparations, 70 biofeedback, 71 bisacodyl, 72 or osmotic laxatives. [73][74][75] While not the focus of this analysis, we noted some statistically significant, but clinically minor, differences in the endpoints between patient cohorts with constipation and IBS-C.…”
Section: Discussionmentioning
confidence: 71%
“…Three pivotal studies have shown significant effects vs placebo on the key symptom of constipation (i.e. more frequent bowel movements), and have also reported positive effects on quality of life and reassuring safety data [22][23][24]. Interestingly, other symptoms associated with constipation, such as bloating, discomfort, a sensation of incomplete bowel movement and excessive straining, have the potential to be improved by treatment [25].…”
Section: Constipationmentioning
confidence: 98%